2016
DOI: 10.1016/j.hjc.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Environment and cardiovascular disease: rationale of the Corinthia study

Abstract: Environmental factors constitute an important but underappreciated risk factor towards the development and progression of cardiovascular disease (CVD). Environmental exposure to variable pollutants is implicated in the derangement or propagation of adverse pathophysiological processes linked with atherosclerosis, including genetic, hemodynamic, metabolic, oxidative and inflammation parameters. However, no data exist on environmental pollution in rural or semi-rural areas. Therefore, the purpose of the "Corinth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Combined, the HHS Hazelinks [ 15 ], Early-Life Followup [ 16 ], Adult Survey [ 17 ] and Cardiovascular Streams aim to provide at least ten years of longitudinal data on the cardiovascular health effects of the six-week PM 2.5 -generating mine fire event. These would complement the 10-year Multi-Ethnic Study of Atherosclerosis and Air Pollution (MESA Air) investigating the relation between CVD and long-term ambient air pollution in a US urban setting [ 45 ], and the 10-year Corinthia study investigating the relation between CVD and environmental factors in rural and semi-rural areas of Greece [ 46 ] as important longitudinal studies contributing to the field of environmental cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…Combined, the HHS Hazelinks [ 15 ], Early-Life Followup [ 16 ], Adult Survey [ 17 ] and Cardiovascular Streams aim to provide at least ten years of longitudinal data on the cardiovascular health effects of the six-week PM 2.5 -generating mine fire event. These would complement the 10-year Multi-Ethnic Study of Atherosclerosis and Air Pollution (MESA Air) investigating the relation between CVD and long-term ambient air pollution in a US urban setting [ 45 ], and the 10-year Corinthia study investigating the relation between CVD and environmental factors in rural and semi-rural areas of Greece [ 46 ] as important longitudinal studies contributing to the field of environmental cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, primary studies have led to the discovery of several P2Y12 polymorphisms that influence ADP-induced platelet activation in healthy subjects [33]. It was suggested that these polymorphisms contribute to a decreased response to clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…The Corinthia study is an epidemiological study with a cross-sectional and prospective longitudinal design. 15 It was carried out from October 2015 to February 2017. Permanent inhabitants of Corinth (n = 2043) aged 40 years or older were voluntarily enrolled.…”
Section: Methodsmentioning
confidence: 99%